PENERAPAN MARKETING MIX TERHADAP BRAND EQUITY PERGURUAN TINGGI SEBAGAI SEBUAH TINJAUAN LITERATUR - Sagala, Roslinda (UNIKA Santo Thomas, 2011)
The process of marketing mix (marketing mix) are successful have a positive impact on brand equity (brand equity). Every marketer trying to take advantage of the marketing mix strategy as a competitive advantage in increasing the brand equity to brand equity owned by the products or services to attract consumers. Level of awareness of a brand into an important cue for consumers to use and specifies a choice of products. In this case, the products you want to achieve is a knowledge-based products (knowledge base). The product was delivered to the college as the core consumer products that are delivered in the marketing of educational services. Many empirical studies have been conducted to investigate to what extent the influence of marketing mix on brand equity colleges, both state college Cleaner (PTN) or private (PTS). However, little empirical research which brings together existing research into a comprehensive literature review that elaborates on the influence of marketing mix on brand equity colleges. Thus, the management of higher education as an educational institution can be categorized on the model management services business model, which factors the marketing mix consists of product, price, place, promotion, people, physical evidence, process can be a key factor in enhancing brand equity college.